2011
DOI: 10.1007/s00296-011-1850-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteochondritis among preparatory and primary school children in an Egyptian governorate

Abstract: Epiphyseal osteochondritis is a localized disorder in childhood. Vascular insufficiency is thought to be the most significant etiologic factor. This study had been carried on Primary and Preparatory school children in Zagazig City and surrounding villages in Sharkia Governorate, Egypt. Total number of studied children were 16,060, 7,380 males, 8,680 females. The mean age was 11.41 ± 1.99. Our results showed that the prevalence of osteochondritis was 21:10,000. Distribution of Sever's and Osgood-Shlatter diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They concluded that OD primarily affects adolescent boys who are active in football and basketball and that it represents a structural response to repeated biomechanical stress. A history of repeated trauma underlying the etiopathogenesis of OD has also been confirmed by Abou El-Soud et al [ 26 ] and De Lucena et al [ 12 ].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…They concluded that OD primarily affects adolescent boys who are active in football and basketball and that it represents a structural response to repeated biomechanical stress. A history of repeated trauma underlying the etiopathogenesis of OD has also been confirmed by Abou El-Soud et al [ 26 ] and De Lucena et al [ 12 ].…”
Section: Resultsmentioning
confidence: 60%
“…Reference lists from the selected papers were also screened. The considered articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] report different factors associated with OD, which are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation